Public Perception of Interfaith Marriage Registration (Across Religions) based on Court Regulations - Sharaja, Alecsius; Gultom, Potler; Gaol, Selamat Lumban (Indonesian Journal of Research in Islamic Studies, 2025)
Background: In Muslim-majority contexts, religious and cultural values significantly shape adolescents' emotional development, particularly in dating-related behaviors, attachment styles, and emotion regulation. Objective: The research aims to examine how dating status influences attachment styles and emotion regulation strategies among Muslim adolescents, considering the impact of religious beliefs and cultural norms. Method: This study employs a systematic literature review approach, synthesizing findings from research conducted between 2017 and 2024. Relevant studies were analyzed to identify patterns in attachment styles and emotion regulation strategies. Results: The findings indicate that non-dating adolescents tend to develop secure attachment patterns and primarily utilize cognitive reappraisal as their emotion regulation strategy. This is reinforced by strong family religious values and structured social support systems. Conclusion: The study underscores the significant role of religious coping mechanisms in fostering emotional resilience and reducing psychological distress among Muslim adolescents. It highlights the importance of structured support systems in shaping secure attachment and adaptive emotion regulation. Contribution: These findings have theoretical, practical, and managerial implications, suggesting the need for faith-based mental health programs, educational interventions, and further cross-cultural research on Muslim adolescent psychology.